The Association between Noncommercial Partnerships and Risk of HIV among Female Sex Workers: Evidences from a Cross-Sectional Behavioral and Biological Survey in Southern India - Renuka Pulikallu Somanath; Ram Manohar Mishra; Niranjan Saggurti; Prabhakar Parimi (AIDS Research and Treatment)
This paper examines the association between female sex workers' (FSWs) noncommercial partnerships with risk of HIV in Andhra Pradesh, India. Data were drawn from a cross-sectional behavioral and biological survey conducted in 2009 among 3225 FSWs from Andhra Pradesh. Participants were asked about their sexual partnerships, condom use, and vulnerability factors and tested for HIV and sexually transmitted infections. The key independent variables considered were presence of a noncommercial sexual partner (no, yes) and the nature of such partnerships (regular, nonregular). FSWs who reported husband as noncommercial partner were considered to have a regular partner, while the rest were defined as having nonregular partners. Adjusted odds ratios (OR) and 95% confidence intervals (CI) were estimated to measure the associations between variables of interest. Almost three-fourths (74.8%) of FSWs reported having noncommercial partners (regular: 55.6%; nonregular: 19.3%). FSWs in nonregular partnerships were more likely to be HIV positive (13.1% versus 10.9%, adjusted OR: 1.4, 95% CI: 1.1–1.8), have syphilis (10.3% versus 4.2%, adjusted OR: 2.3, 95% CI: 1.6–3.3), use condoms inconsistently with occasional clients (21.0% versus 16.5%, adjusted OR: 1.5, 95% CI: 1.2–1.9), and report forced sex (25.1% versus 14.1%, adjusted OR: 1.9, 95% CI: 1.5–2.4) as compared to those in regular partnerships. HIV prevention programs need to emphasize safe sex behaviors, particularly among FSWs who have nonregular partners.